Іван Франко і декаданс - Нестелєєв, Максим; Nestelieiev, Maksym (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті аналізується ставлення І. Франка до декадансу як до літературної течії та типу світогляду. Досліджено трансформацію поглядів на занепадництво в його творчості та збірці «Зів'яле листя» та виявлено значущість естетичної боротьби на порубіжжі століть. The I. Franco's attitude to decadence as a literary movement and his outlook is analyzed in the article. The transformation of views on the decadence in his works and his collection „The Withered Leaves" is researched and revealed the importance of aesthetic struggle on the edge of centuries. Decadence, according to I. Franco, is the works of rich graphomaniac, who support the thesis of „art for art's sake", and he believed, though not always consistently, that this outlook is an anti-Ukrainian and anti-human one. Despite his strong anti-decadent position, I. Franco's „The Withered Leaves" undoubtedly clearly and convincingly reconstructs the individual „sick" mind of decadence, enriching this field of imagery with didacticism and warning while chanting „Іугісаі drama" of lyrical hero. Without taking any decadent and decadence in literature Franco in his collection showed a possible way of life of human being on the edge of the centuries that accepts death as the only possible option.
Ivan Franco and Decadance
Keywords: декаданс; мотив; decadence; motive